The Strategy of Ziswaf Ctarsa Institution in Increasing Public Trust through Social Media - Hani Yuniani; Mike Indarsih; Fajar Diah Astuti; Horidatul Bakiyah; Muhammad Zulfikar (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Public trust is an essential aspect of a non-profit organization like ZISWAF CTARSA. The existence of public trust will increase the amount of public fundraising in the form of zakat, infaq, endowments and sadaqah, which will then be distributed to those in need. Public trust allows the ZISWAF CTARSA institution to carry out its business objectives smoothly. The purpose of this research is to find out the strategy of the ZISWAF CTARSA Institute in increasing public trust and to find out how optimal the content of the ZISWAF CTARSA Institute is in building public trust. The method used is a qualitative method. Sources of data in the form of primary data, namely interviews and observations. And secondary data sources in the form of documentation studies. Data analysis used qualitative techniques, which included inductive, deductive and comparative analysis. The results of the study show that the communication strategies implemented include: a) A team that is specifically responsible for social media management, b) Consistency of communication styles on social media, c) Interesting and trend-following content, d) Digitalization of zakat, e) Open communication with the public through social media and f) Development of artificial intelligence to analyze zakat management and the impact of implementing the program. Then, the primary strategy for creating public trust is by sharing content that contains sharing of success stories and testimonials from beneficiaries. However, this strategy could be more effective. The image of the ZISWAF CTARSA institution is a wish image. The ZISWAF CTARSA Institute runs a business by applying CSR principles, which are its identity and image as a company that aims to be able to help people experiencing poverty and prosper the community equally.